FinTech and SME supply chain efficiency: a scoping review - Che Hassan, Muhammad Hamdi; Osman, Lokhman Hakim (Universiti Teknologi MARA Selangor, 2026)
This scoping review examines how financial technology (FinTech) transforms supply chain operations for Small and Medium Enterprises (SMEs). Analyzing 22 peer reviewed articles, the study identifies key FinTech innovations such as blockchain, peer to peer lending, and digital payment systems and their impact. The analysis reveals seven primary themes where FinTech optimizes SMEs supply chains (1) enhanced risk management via real-time monitoring (2) data driven decision making (3) improved financial accessibility through alternative lending (4) predictive analytics for demand forecasting (5) sustainable supply chain financing (6) increased operational efficiency from automation and (7) strengthened customer relationships on digital platforms. Geographically, research is concentrated in developing economies, with a significant focus on China, highlighting FinTech's strategic role in addressing SMEs challenges in emerging markets. The findings demonstrate FinTech's substantial potential to facilitate faster transactions, improve working capital, and foster financial inclusion. However, barriers like cybersecurity risks, regulatory complexities, and limited digital literacy persist. The review concludes that future research should investigate the long term impacts of FinTech adoption, while policymakers must develop supportive regulatory frameworks. Strategic collaboration between financial institutions and SMEs is crucial to fully realize FinTech transformative potential in building resilient and efficient digital supply chains.